2006
DOI: 10.1017/s0272263106060141
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Corrective Feedback and the Acquisition of L2 Grammar

Abstract: This article reviews previous studies of the effects of implicit and explicit corrective feedback on SLA, pointing out a number of methodological problems. It then reports on a new study of the effects of these two types of corrective feedback on the acquisition of past tense -ed. In an experimental design (two experimental groups and a control group), low-intermediate learners of second language English completed two communicative tasks during which they received either recasts (implicit feedback) or metaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
678
10
16

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 724 publications
(743 citation statements)
references
References 27 publications
39
678
10
16
Order By: Relevance
“…According to Gass and Selinker (2008), feedback can be explicit (teacher stating that there is an error) or implicit (feedback during the course of interaction). Ellis, Loewen, and Erlam, (2006) stated that "CF takes the form of teachers' responses to learner utterances that contain an error. The responses can consist of:…”
Section: Corrective Feedbackmentioning
confidence: 99%
“…According to Gass and Selinker (2008), feedback can be explicit (teacher stating that there is an error) or implicit (feedback during the course of interaction). Ellis, Loewen, and Erlam, (2006) stated that "CF takes the form of teachers' responses to learner utterances that contain an error. The responses can consist of:…”
Section: Corrective Feedbackmentioning
confidence: 99%
“…Interestingly, the SF condition resulted in a very similar accuracy pattern thus emphasizing the role of accuracy feedback in L2 learning. There is some controversy in the L2 literature regarding what type of feedback is most useful to learners, with some studies showing that more explicit forms of feedback (e.g., correction + metalinguistic explanation) are most effective (R. Ellis et al, 2006;Rosa & Leow, 2004) whereas other studies suggest that any type of feedback or just task-essential practice is sufficient (Ferris & Roberts, 2001;Sanz & Morgan-Short, 2004). It is nevertheless reasonable to conclude that some type of feedback is better than none (but see R. Ellis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There is some controversy in the L2 literature regarding what type of feedback is most useful to learners, with some studies showing that more explicit forms of feedback (e.g., correction + metalinguistic explanation) are most effective (R. Ellis et al, 2006;Rosa & Leow, 2004) whereas other studies suggest that any type of feedback or just task-essential practice is sufficient (Ferris & Roberts, 2001;Sanz & Morgan-Short, 2004). It is nevertheless reasonable to conclude that some type of feedback is better than none (but see R. Ellis et al, 2006). Indeed, a study by Mackey and Silver (2005) found that native Chinese-speaking children in Singapore had higher rates of improvement in English question formation when they received corrective feedback (i.e., recasts) than when they did not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations